The Degree of Menstrual Disturbance Is Associated With the Severity of Insulin Resistance in PCOS - Li, Xiaojia; Yang, Dongyong; Pan, Ping; Azziz, Ricardo; Yang, Dongzi; Cheng, Yanxiang; Zhao, Xiaomiao (Frontiers in Endocrinology, 2022)
Objective Insulin resistance (IR) is an important determinant of the phenotype and morbidity of the polycystic ovary syndrome (PCOS). In this study, we aimed to figure out the association between the degree of menstrual disturbance and the severity of IR in women with PCOS. Design It is a cross-sectional study conducted in an academic tertiary setting. Patients The patients comprised five hundred twenty-seven women diagnosed with PCOS by the 2003 Rotterdam criteria and 565 controls with regular vaginal bleeding. Interventions The interventions done for this study are medical history collection, physical examination, and blood sampling. Main outcome measures The main outcome measures are body mass index (BMI), fasting glucose, fasting insulin, homeostatic model assessment for IR (HOMA-IR), and hormonal parameters. Results Women with PCOS had a higher level of BMI, HOMA-IR, and HOMA-β than controls, with a decreased level of sex hormone-binding globulin and QUICK I index. The luteinizing hormone (LH)/follicle-stimulating hormone (FSH), testosterone (T), antral follicle count (AFC), dehydroepiandrosterone sulfate, free androgen index, modified Ferriman–Gallwey score, and the incidence of delayed insulin peak increased with the degree of menstrual disturbance, although there was no significance for the latter four parameters. Women with vaginal bleeding intervals of 45–90 days had a relatively higher level of HOMA-IR and HOMA-β, although it was adjusted with age and BMI than the other two groups. Similar results were observed in AUCI (area under the curve of insulin) and I/G [the ratio of AUCI and AUCG (area under the curve of glucose)]. Anovulatory women with vaginal bleeding episodes of less than 45 days tended to have higher glucose and insulin levels, area under the curve of glucose (AUCG), area under the curve of insulin (AUCI), HOMA-IR, and HOMA-β but decreased QUICK I and Matsuda index than those who were ovulatory. Women with vaginal bleeding intervals of longer than 45 days who had hyperandrogenism (HA) showed a higher level of glucose, insulin, HOMA-IR, and HOMA-β but lower QUICK I and Matsuda Index. Conclusions In women with PCOS, the severity of IR, the LH/FSH ratio, and androgen level increased with a higher degree of disturbance in menstrual cyclicity (i.e., the vaginal bleeding intervals). Subgroup analysis indicated that the situation of HA may aggravate the disorder of glucose metabolism in women with PCOS. Overall, the interval between episodes of vaginal bleeding may be useful as a ready measure for predicting the severity of IR in PCOS.